Impact properties of thin wall ductile iron - Caldera, Martin (2004)
This work studies the impact strength of thin wall ductile iron. The properties of thin wall plates cast on sand moulds of thickness ranging from 2 to 4mm, in which nodule counts ranging from 1 700 to 1 300 nod/mm2 are measured and compared to properties obtained on samples taken from 13 and 25mm Y blocks (ASTM A395), in which regular nodule counts are about 200 nod/mm2. Since standard Charpy specimens could not be machined from the thin plates, some complementary studies were necessary. Impact testing of ductile iron samples of regular nodule count and different widths, showed that the resilience increases noticeably and the ductile-brittle transition temperature drops as the width diminishes. The increase in the nodule count causes a significant decrease in upper shelf resilience, and a decrease in the ductile-brittle transition temperature. Very high nodule count ferritic ductile iron, of nodule count between 1 300 and 1 700 nod/mm2, shows a ductile-brittle transition temperature of approximately -80°C and upper shelf resilience of about 16 J/cm2. A ductile iron of similar chemical composition, but of regular nodule count, shows a transition temperature of approximately -26°C and upper shelf resilience of approximately 18 J/cm2.